Metacognitive Awareness And Use Of Reading Strategies On The Narrative Text By Iraqi EFL College Students - alQatrani, Munif Y. Dhaher (2012)

(untitled)
The aim of this study is to examine EFL readers' metacognitive awareness level of reading strategies and use of reading strategies to comprehend the narrative text. The study was done in Basrah University, Iraq and the respondents are Arabic students in the College of Education – Department of English language. The study was carried out by giving the students a questionnaire to investigate their awareness of reading strategies which is an Arabic translated version of Metacognitve Awareness of Reading Strategies Inventory (MARSI) and a reading comprehension exercise. The correlation between good and poor readers' awareness of reading strategies in comprehension of the narrative text was investigated.